(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
The present work aims at describing the workflow applied for the use of AM technologies during the worst phase of Covid-19 emergency. AM technologies have proved to be effective for the production in short time of many components to be used within ventilation systems, and which rapidly run out of stock due to unprecedent high demand. Moreover, many systems required modifications to prevent personnel’s infection. We report the workflow applied to face production needs, in terms of materials and technologies selection according to the specific requirements (disinfection, device criticality) and some practical examples.